Effect of Climatic Variability on Population Dynamics of Insect Pests and Natural Enemies in Linseed (Linum usitatissimum L.) - Sahoo, S. K. (International Journal of Bio-resource and Stress Management, 2023)
The influence of climatic variability on the insect pests of linseed and their natural enemies were investigated during rabi seasons of the year 2011-12, 2012-13 and 2013-14 at Berhampore, West Bengal, India. During the course of investigation four insect pests namely bud fly, termite, thrips and jassids along with two natural enemies (lady beetle and spider) were noticed at various growth stages of linseed crop. The infestation due to bud fly, termite, thrips and jassids were recorded upto 41% bud damage, 18% cut, 9 thrips plant-1 and 4 jassids plant-1, respectively. Last week of February was most suited for multiplication of bud fly and thrips. Infestation of termite initiated during maturity stage of the crop with the maximum damage at 10th Standard Meteorological Week when soil was dry and they attacked at the basal portion of the crop. The correlation worked out between insect pests and natural enemies with the weather parameters revealed significant positive correlation with the temperature but negatively correlated with relative humidity. It is revealed from the step wise regression equation that combined effect of all weather parameters had more influence on insect pests population and except maximum temperature none of the weather factor alone had much more effect on them. The combined influence of rainfall, temperature and relative humidity on bud fly, termite, thrips and jassids population increased with R2 value of 0.782, 0.651, 0.779 and 0.857, respectively.